The Effect Of Investment Decisions, Funding Decisions And Dividend Policy On Firm Value In The Banking Industry Listed On The Bei For The Period 2021-2023: - Nasrudin, Nasrudin (Dinasti International Journal of Digital Business Management, 2023)
This research aims to determine the influence of investment decisions, funding decisions and dividend policies in the banking industry listed on the IDX for the 2021-2023 period. By using samples using purposive sampling techniques from 10 companies and multiple regression analysis, the research results show that investment decisions have a positive impact and have a significant effect on company value, while funding decisions and dividend policies do not have a significant effect on company value. In this study, researchers suggest that companies and managers pay attention to important decisions within the company to increase company value.